THE IMPACTS OF THE DEMOGRAPHIC CHARACTERISTICS OF RESIDENTS ON THE PERCEPTION OF QUALITY OF OFF-CAMPUS STUDENT ACCOMMODATION IN SOUTH-SOUTH, NIGERIA - O.C. BELLA-OMUNAGBE; Winston SHAKANTU; Marle VAN EYK; Amanda WERNER (Journal of Construction Project Management and Innovation)
This study presents the findings of the evaluation of the impacts of the demographic characteristics of residents on the perception of quality of off-campus accommodation. It is limited to students who are currently residing in privately developed off-campus accommodation in selected universities, towns and cities in South-South, Nigeria. The data for this study were gathered between June and August, 2014 with the used of self-study structured questionnaire. A total of 520 respondents participated in the survey. The findings of the study revealed that though the demographic characteristics of students are essential in the determination of perception of quality of attributes of housing, the degree of influence differs among gender, age groups, income levels and the years of study of students. The influence of age, gender, income and year of study on the perception of quality of off-campus accommodation were also found to be statistically significant. The main implication of these findings is that investors in the student housing market can segment the  development of off-campus accommodation to serve a selected demographic group(s).